Identification of KIT and BRAF mutations in thyroid tissue using next-generation sequencing in an Ecuadorian patient: A case report - Cadena-Ullauri, Santiago; Paz-Cruz, Elius; Tamayo-Trujillo, Rafael; Guevara-Ramírez, Patricia; Ruiz-Pozo, Viviana; Solis-Pazmino, Paola; Garcia, Cristhian; Godoy, Richard; Lincango-Naranjo, Eddy; Zambrano, Ana Karina (Frontiers in Oncology, 2023)
Background: The incidence of thyroid cancer has increased worldwide. Ecuador presents the highest incidence among Latin American countries and the second around the world. Genetic alteration is the driving force for thyroid tumorigenesis and progression. The change from valine (V) to glutamic acid (E) at codon 600 of the BRAF gene (BRAFVal600Glu) is the most commonly reported mutation in thyroid cancer. Moreover, the BRAF mutation is not the only mutation that has been correlated with TC. For instance, mutations and overexpression of the KIT gene has been associated with different types of cancer, including lung and colon cancer, and neuroblastoma. Case presentation: A woman in her early fifties, self-identified as mestizo, from Otavalo, Imbabura-Ecuador had no systemic diseases and denied allergies, but she had a family history of a benign thyroid nodule. Physical examination revealed a thyroid gland enlargement. The fine-needle aspiration biopsy indicated papillary thyroid cancer. The patient underwent a successful total thyroidectomy with an excellent recovery and no additional treatments after surgery. Using Next-Generation sequencing a heterozygous mutation in the BRAF gene, causing an amino acid change Val600Glu was identified. Similarly, in the KIT gene, a heterozygous mutation resulting in an amino acid change Leu678Phe was detected. Moreover, an ancestry analysis was performed, and the results showed 3.1% African, 20.9% European, and 76% Native American ancestry. Conclusions: This report represents the genetic characteristics of papillary thyroid cancer in an Ecuadorian woman with a mainly Native American ethnic component. Further studies of pathological variants are needed to determine if the combined demographic and molecular profiles are useful to develop targeted treatments focused on the Ecuadorian population.